Trompeuses séductions. La Chute d’Icare des Musées royaux des Beaux-Arts de Belgique - Dominique Allart; Christina Currie (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The scientific examination of the Fall of Icarus of the Royal Museums of Fine Arts of Belgium in Brussels leads to the conclusion that the work is not by the hand of Pieter Bruegel the Elder, as with a second version in the Van Buuren Museum (Brussels). The painting is no doubt a copy after a lost original by the artist. The analysis of a cross-section of the paint layer and radiocarbon dating of the canvas suggest that it is an old copy. Under the worn and retouched paint layer, camouflaged by a yellowed varnish, the infrared reflectogram reveals a studious and clumsy underdrawing that is neither characteristic of Pieter Bruegel the Elder nor of Pieter Brueghel the Younger, his elder son and primary copyist. The poor condition of the painting hinders any attempt at attribution, but this should not prevent its admirers from continuing to savour its mysterious charms.